PENGARUH LOKASI PROPERTI, JENIS PROPERTI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MELALUI DIGITAL MARKETING - Imas Sukaesih; Rosyid Rosyid; Siti A. Immawati (POLITEKNIK LP3I JAKARTA, 2023)
The Property business in Indonesia, especially in Jabodetabek, still has a good opportunity where there is still a lot of strategic land to be developed and the general public is looking for property that is not only for residential but also for long-term investment. This study was conducted to determine the effect of property location, property type and service quality on consumer purchasing decisions through digital marketing as an intervening variable, a case study of PT Trinitiland Tbk located in Tangerang. The long-term goal to be achieved from the results of this study is to develop a learning model by considering residential and building marketing strategies on Collins Boulevard. The research method used is a quantitative method to explore and reveal the process. The research subjects are prospective consumers or consumers of Collins Boulevard Serpong Tangerang. Analysis of research data using quantitative data analysis is an effort made by working with data, organizing data, sorting it into manageable units, synthesizing it, searching for and finding what is important and what will be learned. The results of the analysis show that either partially or simultaneously the location of the property, the type of property and the quality of service on digital marketing and purchasing decisions have a positive and significant effect. Keywords : Property Location, Type Of Property, Quality Of Service For Purchasing Decisions, Digital Marketing